2004
DOI: 10.1016/j.rapm.2004.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal baclofen in pain management

Abstract: Baclofen is a GABA(B) agonist that is administered spinally via an implanted drug delivery device to treat spasticity. It has been shown to have powerful antinociceptive effects in experimental animal models at doses that produce little or no motor-blocking effects but has rarely been used as a spinal analgesic agent in patients without spasticity. Several studies have indicated that intrathecal baclofen provides relief of central pain in patients with spasticity. To date, only 3 studies have shown it to be ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
42
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 57 publications
(64 reference statements)
0
42
0
Order By: Relevance
“…Of particular interest are the respective contributions of the baclofen-responsive and the DAMGO-responsive lamina II neurons to intrathecal antinociception. Our observations suggest that overlapping but distinct spinal circuits mediate the antinociceptive effects of intrathecal opioids and baclofen and may explain why modulating both circuits in intrathecal drug therapy is most effective for treating certain patients and certain types of pain (Slonimski et al, 2004).…”
Section: Discussionmentioning
confidence: 80%
“…Of particular interest are the respective contributions of the baclofen-responsive and the DAMGO-responsive lamina II neurons to intrathecal antinociception. Our observations suggest that overlapping but distinct spinal circuits mediate the antinociceptive effects of intrathecal opioids and baclofen and may explain why modulating both circuits in intrathecal drug therapy is most effective for treating certain patients and certain types of pain (Slonimski et al, 2004).…”
Section: Discussionmentioning
confidence: 80%
“…In addition, GABA B agonists cause inhibition of calcium conductance across voltage-gated Ca 2+ channels and decrease the evoked release of excitatory neurotransmitters. Also, baclofen can attenuate pain perception by affecting pain transmission systems, suppress neuropathic pain, down-regulate the sympathetic nervous system, and decrease pain associated with muscle spasms [4]. Intrathecal infusion of baclofen has been used to treat spasticity since the 1980s [10].…”
Section: Discussionmentioning
confidence: 99%
“…Intrathecal baclofen (ITB) pumps have been used to ameliorate global pain in patients with CRPS and dystonia based on the anti-nociceptive effects of ITB [2][3][4][5]. Furthermore, several studies have reported the clinical effectiveness of combined SCS and ITB pump therapy as a multimodal therapeutic approach [3,5].…”
mentioning
confidence: 99%
“…The antispastic properties of baclofen are mediated by the suppression of release of excitatory neurotransmitters and inhibition of excitatory afferent terminals involved in monosynaptic and polysynaptic reflex activity at the spinal cord level [16][17]. Only recently, the antinociceptive effects of intrathecal baclofen, independent of motor blockade, have been suggested [18][19]. Zuniga et al [18] reported two cases of advanced CRPS successfully treated with intrathecal baclofen.…”
Section: Discussionmentioning
confidence: 99%
“…Zuniga et al [18] reported two cases of advanced CRPS successfully treated with intrathecal baclofen. A recent review by Slonimski et al [19] suggests efficacy of intrathecal baclofen for nociceptive and neuropathic pain, particularly in combination with opioid and/or clonidine.…”
Section: Discussionmentioning
confidence: 99%